Lukiškės remand Prison-closed prison during the Nazi occupation period (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2019)
On July the 2nd 2019, the activity of Lukiškės Remand Prison-Closed Prison came to an end officially. It was a prison situated in the centre of Vilnius for 115 years. The article focuses on the historical events, tragical even for the history of Lukiškės prison – the period of the Nazi occupation (1941–1944). This subject has not attracted attention of the researchers-historians so far. No Lithuanian historiography methods have been applied to this topic specifically. The history of this institution is investigated here at the following angles: the stats of prisoners (changes in prisoner numbers, imprisonment and release of detainees), composition of inmates by nationality, gender, offence type (political or criminal prisoners), system of punishments, imprisonment conditions, catering and health problems of the detainees, behaviour of prison employees against detainees and prison escape events.
Keywords: Lithuania; German occupation; repressions; Lukiškės prison